Flammability Assessment of Multi-Layered Fabrics (Journal of Fiber Bioengineering and Informatics, 2024)
Fabric flammability is influenced by factors such as the composition of the fibre material, the manufacturing process and additional chemical treatments that are applied. These variables make it difficult topredict the nature and intensity of a clothing fire and the risk of injury associated with flame exposure.The severity of an injury will depend on the duration of the exposure and the temperature of theflames. This investigation aimed to identify the flaming characteristics of multi-layered fabric samples,which have not been reported extensively in the literature. Ninety fabric samples were used in this study,including cotton, wool, polyester, nylon and silk. The tests were conducted inside a controlled laboratoryenvironment. The results revealed that fabric flame temperatures and burn times for wool, polyester,nylon and silk decreased significantly with adding one and two fabric layers. This appears to representa “protective factor” against burn injury. However, the Cotton samples exhibited the opposite. Themaximum flame temperature and combustion times were increased when additional layers were applied.Therefore, it is necessary to perform flammability tests that include multiple layers of fabric materialwhen assessing the potential for fire injury in clothing.